IMPLEMENTASI COMPUTATIONAL THINKING PADA KURIKULUM MERDEKA MENGGUNAKAN METODE UNPLUGGED PROGRAMMING ACTIVITY (UPA) - Sutojo, T.; Rustad, Supriadi; Akrom, Muhamad; Herowati, Wise (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2024)
The application of Computational Thinking (CT) in the Kurikulum Merdeka is one way to strengthen fundamental competencies and holistic understanding in education. CT skills can be taught through Unplugged Programming Activities (UPA), which is an approach to teaching CT skills without using computer tools. This approach is appropriate for schools that do not have adequate technological infrastructure and for the little ones, namely students under 9 years of age. This service aims to provide UPA method training for teachers at Gaussian Kamil School (GKS) so that it can be applied to the Merdeka Curriculum at GKS. The UPA activity materials used were the games "Bee-bot" and "My Robotic Friends Activity". It is hoped that this material can provide knowledge and skills regarding CT to training participants at GKS. The results of the pre-test and post-test evaluation showed an increase in scores before and after the training process for the participants. So it can be said that the results of this service show that the UPA method is suitable for use to teach CT skills in schools that do not have adequate technological infrastructure.